Preparation method of mesoporous quartz
By using quartz ore or special minerals containing quartz, combined with steps such as dispersion, ultra-fine grinding, micro-sintering, calcination and acid leaching, mesoporous quartz materials with high specific surface area and high mesopore volume ratio are prepared, solving the existing problems. In order to solve the problems of complex process, high cost and waste liquid pollution, the preparation of environmentally friendly and low-cost mesoporous quartz materials has been achieved.
Patent Information
- Application Number
- CN202411433854.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, the process of preparing mesoporous silicon materials is complex and costly, and the use of a variety of organic agents in chemical synthesis methods leads to waste liquid contamination.
Using quartz ore or special minerals containing quartz as raw materials, mesoporous quartz materials with high specific surface area and high mesopore volume ratio are prepared through steps such as dispersion, ultra-fine grinding, micro-sintering, calcination and acid leaching.
Realizing low preparation costs, environmentally friendly process, and easy industrialization of Ji Kong quartz materials, and retaining the crystal structure of quartz, it has better acidic and alkali resistance, high temperature resistance, and corrosion resistance.
Smart Images

Figure CN119330362A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mineral processing, more specifically, to a technical method for preparing mesoporous quartz material by using quartz ore or special minerals containing quartz, and in particular to a method for preparing mesoporous quartz. Background Art
[0002] Mesoporous materials have received special scientific attention due to their high surface area, uniform porosity on different length scales, high volume storage capability, shape selectivity, and enhanced mass transport and diffusion. These materials have been widely used in catalysis, separation, adsorption, photovoltaic solar cells, energy storage and conversion, chemical sensing, and drug delivery.
[0003] Mesoporous silica materials have attracted much attention from scholars because of their excellent adsorption performance. This type of material has an ordered pore structure, a single and adjustable pore size, and a variety of pore morphologies. These excellent properties make mesoporous silica materials occupy an important position in adsorption separation technology, biomedical applications, environmental protection, and industrial catalytic processes. Due to the excellent surface characteristics of mesoporous silica materials, components with catalytic effects can be loaded in the pores of mesoporous silica materials, providing an ideal support link for the catalyst and accelerating the catalytic process. At the same time, the large pore size channels of mesoporous silica materials make them good drug carriers in biomedicine.
[0004] At present, the methods for preparing mesoporous silicon materials are mainly chemical synthesis methods, including sol-gel method, hydrothermal synthesis method, template method, room temperature synthesis method, microwave synthesis method, solvent evaporation method, non-aqueous synthesis method, wet gel roasting method, phase transition method, etc. These synthesis methods usually divide the preparation process of mesoporous silicon materials into two parts: the establishment of organic-inorganic liquid crystal phase and the generation of mesoporous channels. In the actual production process, the preparation process of mesoporous silicon materials is complicated and costly. Since a variety of organic agents are used in the process, the waste liquid generated is also polluting to the environment. Summary of the invention
[0005] In order to solve the technical defects and deficiencies in the prior art, the present invention provides the following technical solutions: a method for preparing mesoporous quartz, which can use quartz ore or special minerals containing quartz to prepare mesoporous quartz materials with good crystallization and high specific surface area, improve the application performance and use value of quartz ore or special minerals containing quartz, use quartz ore or special minerals containing quartz as raw materials, obtain mesoporous quartz materials with a specific surface area of 30m 2 / g or above, the volume of mesopores accounts for more than 50%, and it has the advantages of simple processing technology, low cost and easy industrialization.
[0006] The present invention provides a method for preparing mesoporous quartz, comprising the following steps:
[0007] S1, preparing slurry;
[0008] S2, repeatedly superfine grinding the slurry;
[0009] S3, preparation of mesoporous quartz sintered samples;
[0010] S4, subjecting the mesoporous quartz sintered sample to acid leaching, washing and drying to form honeycomb quartz.
[0011] Preferably, the S1 comprises:
[0012] S11, with d 95 Quartz ore with a diameter of less than 74 μm or special minerals containing quartz is used as raw material and added into a certain amount of water to form a first mixture;
[0013] S12, adding a proper amount of grinding aid and barrier agent to the first mixture, stirring and breaking up the mixture in a high-speed stirring disperser to form a slurry.
[0014] Preferably, the mass ratio of the quartz ore or special mineral containing quartz: water: grinding aid: barrier agent is
[0015] =100:(100~800):(0.5~5):(10~50).
[0016] Preferably, the grinding aid includes sodium polyacrylate, triethanolamine or sodium hexametaphosphate; the barrier agent is nano zinc oxide or nano calcium carbonate; the particle size range of the barrier agent is 2 to 50 nm; the stirring and breaking speed is 800-1200 rpm, and the stirring and breaking time is 0.5h-4h.
[0017] Preferably, S2 includes:
[0018] S21, pumping the slurry into a vertical stirred mill and adding grinding media to form a material;
[0019] S22, repeatedly superfine grinding the material until d 90 <0.7μm to form a mixture slurry.
[0020] Preferably, the grinding media are alumina ceramic beads or zirconia ceramic beads; the size of the grinding media is Φ0.5-5 mm, and the filling rate of the grinding media in the grinding cavity is 65%-80%.
[0021] Preferably, S3 includes:
[0022] S31, filtering the mixture slurry to form a filter cake;
[0023] S32, drying and breaking up the filter cake to form bulk material;
[0024] S33, performing micro-sintering and calcining treatment on the bulk material in a muffle furnace to form a mesoporous quartz sintered sample.
[0025] Preferably, the temperature of the micro-sintering and calcining treatment is 700-1100° C., and the constant temperature time of the micro-sintering and calcining treatment is 0.5-3 hours.
[0026] Preferably, S4 includes:
[0027] S41, placing the mesoporous quartz sintered sample into a plastic storage tank, adding hydrochloric acid for acid leaching to obtain an acid-leached sample, wherein the acid leaching is used to remove excess barrier agent;
[0028] S42, washing the acid-leached sample multiple times until the washing solution is in a neutral condition to obtain a neutral sample;
[0029] S43, drying the neutral sample to obtain the mesoporous quartz; wherein the specific surface area of the mesoporous quartz is 30m 2 / g or more, and the volume of mesopores accounts for more than 50%.
[0030] Preferably, the mass ratio of the mesoporous quartz sintered sample to the hydrochloric acid is 100:(20-50), and the acid leaching time is 1-24 hours.
[0031] Beneficial effects of the present invention:
[0032] (1) Innovative use of quartz ore or special minerals containing quartz as raw materials to prepare mesoporous quartz materials, which has not been reported in existing literature, and innovative use of micro-sintering technology to prepare mesoporous quartz materials, which can preserve the crystal structure of quartz more completely, and have better acid and alkali resistance, high temperature resistance, and corrosion resistance than amorphous mesoporous silicon materials. Compared with general chemical synthesis preparation processes (sol-gel method, hydrothermal synthesis method, template method), this method has the advantages of low cost, environmentally friendly process, easy industrialization, etc., and can ensure the crystal structure of quartz, and can have good performance in catalytic adsorption, biomedicine, battery energy storage and other fields.
[0033] (2) The processing method has a simple process flow, and mesoporous quartz material can be obtained by breaking up, ultrafine grinding, and micro-sintering and calcining. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The present invention provides a flow chart of the method for preparing the mesoporous quartz product.
[0035] Figure 2 The flowchart of step S1 provided by the present invention.
[0036] Figure 3 This is a flow chart of step S2 provided by the present invention.
[0037] Figure 4 The flowchart of step S3 provided by the present invention.
[0038] Figure 5 The flowchart of step S4 provided by the present invention.
[0039] Figure 6 This is a SEM image of the mesoporous quartz material prepared in the present invention.
[0040] Figure 7 This is the XRD (scanning electron microscope) image of the mesoporous quartz material prepared in the present invention. DETAILED DESCRIPTION
[0041] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0042] like Figure 1-5 As shown, this embodiment provides a method for preparing a honeycomb quartz product, comprising the following steps:
[0043] S1, preparing slurry;
[0044] As a preferred embodiment, the S1 includes:
[0045] S11, with d 95 Quartz ore with a diameter of less than 74 μm or special minerals containing quartz is used as raw material and added into a certain amount of water to form a first mixture;
[0046] S12, adding an appropriate amount of grinding aid and barrier agent to the first mixture, and stirring and breaking the mixture in a high-speed stirring disperser to form a slurry; the particle size in the slurry is the same as that of the raw material, because the stirring and breaking step does not affect the particle size.
[0047] As a preferred embodiment, the mass ratio of the quartz ore or special mineral containing quartz: water: grinding aid: barrier agent is
[0048] =100:(100~800):(0.5~5):(10~50);
[0049] As a preferred embodiment, the grinding aid includes sodium polyacrylate, triethanolamine or sodium hexametaphosphate; the barrier agent is nano zinc oxide or nano calcium carbonate; the particle size range of the barrier agent is 2 to 50 nm; the stirring and breaking speed is 800-1200 rpm, and the stirring and breaking time is 0.5h-4h.
[0050] The amount of water and grinding aid in the ratio can improve the grinding efficiency, bringing advantages in energy consumption and product particle size. The amount of barrier agent affects the subsequent specific surface area. Adding more barrier agent will obtain a larger specific surface area, but it will also cause the sample strength to decrease. Therefore, as a more preferred embodiment, the grinding aid is sodium polyacrylate, the barrier agent is nano-calcium carbonate, and the particle size of the barrier agent is 5-10nm; the mass ratio of the quartz ore or special mineral containing quartz: water: grinding aid: barrier agent = 100: (100-300): (1.5-2.5): (30-50), the stirring and breaking speed is 1000 rpm, and the stirring and breaking time is 0.5h-2h.
[0051] S2, repeatedly superfine grinding the slurry;
[0052] As a preferred embodiment, S2 includes:
[0053] S21, pumping the slurry into a vertical stirred mill and adding grinding media to form a material;
[0054] As a preferred embodiment, the grinding media are alumina ceramic beads or zirconia ceramic beads; the size of the grinding media is Φ0.5-5 mm, and the filling rate of the grinding media in the grinding cavity is 65%-80%.
[0055] Among the dielectric materials, alumina is cheap, but it is easy to introduce impurity elements for pollution, while zirconium oxide is expensive and less polluting. The smaller the size, the higher the grinding efficiency, and the smaller the particle size obtained. The filling rate is related to the heat generation and grinding effect during the grinding process. Generally, the higher the filling rate, the better the grinding effect, but too high a filling rate will lead to a sharp increase in energy consumption, and the equipment will heat up seriously, causing the grinding aid to fail. Therefore, as a more preferred embodiment, the grinding medium material is zirconium oxide ceramic beads, the size of the zirconium oxide ceramic beads is Φ1mm~3mm, and the filling rate of the zirconium oxide ceramic beads in the grinding cavity is 70%~80%.
[0056] S22, repeatedly superfine grinding the material until d 90 <0.7μm to form a mixture slurry.
[0057] S3, preparation of mesoporous quartz sintered samples;
[0058] As a preferred implementation, S3 includes:
[0059] S31, filtering the mixture slurry to form a filter cake;
[0060] S32, drying and breaking up the filter cake to form bulk material;
[0061] S33, the bulk material is subjected to micro-sintering and calcining treatment in a muffle furnace to form a mesoporous quartz sintered sample; in this embodiment, the constant temperature time is the time for keeping the temperature after the calcination reaches the specified temperature, and the time of the heating process is not included; the sample obtained by complete sintering is a ceramic, which is dense and will produce a molten phase during the sintering process, and the micro-sintering can be reflected by the surface area and the pore structure.
[0062] As a preferred embodiment, the temperature of the micro-sintering and calcining treatment is 700-1100° C., and the constant temperature time of the micro-sintering and calcining treatment is 0.5-3 hours.
[0063] If the calcination temperature is too high, the product will be dense and lose specific surface area. If the temperature is not high enough, the molten phase cannot be generated, resulting in sintering failure. The same is true for the calcination time. The calcination time is shorter at high temperature, while it takes a long time at low temperature. Therefore, as a more preferred embodiment, the temperature of the micro-sintering calcination treatment is 800-1000°C, and the constant temperature time of the micro-sintering calcination treatment is 1.5-3h.
[0064] S4, performing acid leaching, washing and drying treatment on the mesoporous quartz sintered sample to form mesoporous quartz;
[0065] As a preferred implementation, S4 includes:
[0066] S41, placing the mesoporous quartz sintered sample into a plastic storage tank, adding hydrochloric acid for acid leaching to obtain an acid-leached sample, wherein the acid leaching is used to remove excess barrier agents and sintering aids;
[0067] As a preferred embodiment, the mass ratio of the mesoporous quartz sintered sample to the hydrochloric acid is 100:(20-50), and the acid leaching time is 1-24 hours.
[0068] In acid leaching, increasing the proportion of acid will increase the cost, and the amount of washing water will also increase during the acid cleaning process. However, the purification effect is better with increasing the acid proportion. Longer acid leaching time also has better effects, but the production efficiency is low. Therefore, as a more preferred embodiment, the mass ratio of the mesoporous quartz sintered sample to the hydrochloric acid is 100: (30-40), and the acid leaching time is 5-12 hours.
[0069] S42, washing the acid-leached sample multiple times until the washing solution is in a neutral condition to obtain a neutral sample;
[0070] S43, drying the neutral sample to obtain the mesoporous quartz; wherein the specific surface area of the mesoporous quartz is 30m 2 / g or more, and the volume of mesopores accounts for more than 50%.
[0071] Application Examples
[0072] Example 1
[0073] This embodiment provides a method for preparing a mesoporous quartz material, comprising the following steps:
[0074] 1) With d 90 =6.08μm powder quartz ore is used as raw material, a certain amount of water, sodium polyacrylate grinding aid and calcium carbonate barrier agent are added, and the mixture is dispersed in a high-speed stirring disperser for 1h.
[0075] Ratio: powdered quartz: water: grinding aid: barrier agent
[0076] =100:200:2:50.
[0077] 2) Pump the slurry prepared in 1) into a vertical stirred mill for ultrafine grinding. Use Φ2.2mm alumina ceramic beads as grinding media with a filling rate of 70%. Grind the material repeatedly for 12 times. 90 =0.63μm.
[0078] 3) The submicron quartz powder slurry prepared in 2) is filtered, dried and broken up, and then calcined in a muffle furnace at a calcination temperature of 700° C. for a constant temperature time of 2 h.
[0079] 4) The sample prepared in 3) was placed in a plastic storage tank, and hydrochloric acid was added for purification.
[0080] Ratio: powder quartz: hydrochloric acid = (100:20), acid leaching time 16h.
[0081] 5) After the acid leaching is completed, the filter washing is performed several times until the washing water is neutral, and then filtered and dried to obtain a mesoporous quartz material with a specific surface area of 69.73m 2 / g, and the volume of mesopores accounts for 60.48%.
[0082] Example 2
[0083] This embodiment provides a method for preparing a mesoporous quartz material, comprising the following steps:
[0084] 1) With d 90 =6.32μm powder quartz ore is used as raw material, a certain amount of water, sodium polyacrylate grinding aid and calcium carbonate barrier agent are added, and the mixture is dispersed in a high-speed stirring disperser for 2h.
[0085] Ratio: powdered quartz: water: grinding aid: barrier agent
[0086] =100:800:2.5:50.
[0087] 2) Pump the slurry prepared in 1) into a vertical stirred mill for ultrafine grinding. Use Φ5mm alumina ceramic beads as grinding media with a filling rate of 80%. Grind the material repeatedly for 12 times. 90 =0.68μm.
[0088] 3) The submicron quartz powder slurry prepared in 2) is filtered, dried and broken up, and then calcined in a muffle furnace at a calcination temperature of 1100° C. for a constant temperature time of 0.5 h.
[0089] 4) The sample prepared in 3) was placed in a plastic storage tank, and hydrochloric acid was added for purification.
[0090] Ratio: powder quartz: hydrochloric acid = (100:50), acid leaching time 5h.
[0091] 5) After the acid leaching is completed, the filter washing is performed several times until the washing water is neutral, and then filtered and dried to obtain a mesoporous quartz material with a specific surface area of 56.80 m 2 / g, and the volume of mesopores accounts for 52.68%.
[0092] Example 3
[0093] This embodiment provides a method for preparing a mesoporous quartz material, comprising the following steps:
[0094] 1) With d 90 =5.19μm quartz powder is used as raw material, a certain amount of water, sodium polyacrylate grinding aid and calcium carbonate barrier agent are added, and the mixture is dispersed in a high-speed stirring disperser for 2h.
[0095] Ratio: Quartz powder: Water: Grinding aid: Barrier agent
[0096] =100:100:0.5:1.
[0097] 2) Pump the slurry prepared in 1) into a vertical stirred mill for ultrafine grinding. Use Φ0.5mm zirconium oxide ceramic beads as grinding media with a filling rate of 65%. Grind the material repeatedly for 10 times. 90 =6.11μm.
[0098] 3) The submicron quartz powder slurry prepared in 2) is filtered, dried and broken up, and then calcined in a muffle furnace at a calcination temperature of 900° C. for 3 h.
[0099] 4) The sample prepared in 3) was placed in a plastic storage tank, and hydrochloric acid was added for purification.
[0100] Ratio: powder quartz: hydrochloric acid = (100:40), acid leaching time 8h.
[0101] 5) After the acid leaching is completed, the filter washing is performed several times until the washing water is neutral, and then filtered and dried to obtain a mesoporous quartz material with a specific surface area of 76.74 m 2 / g, and the volume of mesopores accounts for 61.97%.
[0102] The above embodiments grind quartz ore or special minerals containing quartz to submicron level, innovatively use micro-sintering process to produce mesoporous channels, and utilize the characteristics of quartz sintering process to realize the preparation of mesoporous quartz. This is the first report of crystalline mesoporous silicon material, avoiding the problems of low raw material utilization and complex process in chemical synthesis. The process of the present invention is more environmentally friendly than chemical synthesis of mesoporous silicon materials, and is suitable for large-scale production, simple process and low cost. The prepared mesoporous silicon material is mesoporous quartz with better crystallization, in which the silicon dioxide component exists in the form of α-quartz, and the performance in acid and alkali resistance, high temperature resistance, corrosion resistance and other aspects will be better than amorphous mesoporous silicon materials.
[0103] like Figure 6 As shown, the abscissa in the XRD graph represents the 2theta angle, and the ordinate represents the signal intensity. The XRD graph shows that the sintered sample still has a very good quartz crystal structure.
[0104] like Figure 7 As shown, for a standard quartz card, the scanning electron microscope image shows that the particles grow together after the sintering process to form a mesoporous structure.
[0105] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing mesoporous quartz, characterized in that: The steps include: S1, preparing slurry; S2, repeatedly superfine grinding the slurry; S3, preparation of mesoporous quartz sintered samples; S4, subjecting the mesoporous quartz sintered sample to acid leaching, washing and drying to form honeycomb quartz.
2. The method for preparing mesoporous quartz according to claim 1, characterized in that: The S1 includes: S11, with d 95 Quartz ore with a particle size less than 74 μm or special minerals containing quartz are used as raw materials and added into a certain amount of water to form a first mixture; S12, adding a proper amount of grinding aid and barrier agent to the first mixture, stirring and breaking up the mixture in a high-speed stirring disperser to form a slurry.
3. The method for preparing mesoporous quartz according to claim 2, characterized in that: The mass ratio of the quartz ore or special mineral containing quartz: water: grinding aid: barrier agent is 100: (100-800): (0.5-5): (10-50).
4. The method for preparing mesoporous quartz according to claim 3, characterized in that: The grinding aid includes sodium polyacrylate, triethanolamine or sodium hexametaphosphate; the barrier agent is nano zinc oxide or nano calcium carbonate; the particle size range of the barrier agent is 2 to 50 nm; the stirring and breaking speed is 800-1200 rpm, and the stirring and breaking time is 0.5h-4h.
5. The method for preparing mesoporous quartz according to claim 4, characterized in that: The S2 includes: S21, pumping the slurry into a vertical stirred mill and adding grinding media to form a material; S22, repeatedly superfine grinding the material until d 90 <0.7μm to form a mixture slurry.
6. The method for preparing mesoporous quartz according to claim 5, characterized in that: The grinding media are alumina ceramic beads or zirconia ceramic beads; the size of the grinding media is Φ0.5-5mm, and the filling rate of the grinding media in the grinding cavity is 65%-80%.
7. The method for preparing mesoporous quartz according to claim 6, characterized in that: The S3 includes: S31, filtering the mixture slurry to form a filter cake; S32, drying and breaking up the filter cake to form bulk material; S33, performing micro-sintering and calcining treatment on the bulk material in a muffle furnace to form a mesoporous quartz sintered sample.
8. The method for preparing mesoporous quartz according to claim 7, characterized in that: The temperature of the micro-sintering and calcining treatment is 700-1100° C., and the constant temperature time of the micro-sintering and calcining treatment is 0.5-3 hours.
9. The method for preparing mesoporous quartz according to claim 8, characterized in that: The S4 includes: S41, placing the mesoporous quartz sintered sample into a plastic storage tank, adding hydrochloric acid for acid leaching to obtain an acid-leached sample, wherein the acid leaching is used to remove excess barrier agent; S42, washing the acid-leached sample multiple times until the washing liquid is in a neutral condition to obtain a neutral sample; S43, drying the neutral sample to obtain the mesoporous quartz; wherein the specific surface area of the mesoporous quartz is 30m 2 / g or more, and the volume of mesopores accounts for more than 50%.
10. The method for preparing mesoporous quartz according to claim 9, characterized in that: The mass ratio of the mesoporous quartz sintered sample to the hydrochloric acid is 100:(20-50), and the acid leaching time is 1-24 hours.